Analysis of the epistemological assumptions that shaped environmental communication and the opportunity for discipline reconstruction - Cuesta Moreno, Oscar Julián (2016)
This article analizes the epistemological assumptions that have shaped the environmental communication (EC) in Spain and Latin America. It was established that Iberoamerican authors who have studied the EC do not consider the notion of environment; they are limited to presenting strategies which promote environmentally- friendly behaviors. In addition, this article proposes the EC notion of environment to be extended, resorting to the categories of relationality, enaction and the Good Living. Finally, this article recommends environmental communicators to cultivate a self-analysis enabling them to identify biological and cultural heritages which, unconsciously, shape their notion of environment and their relation with nature.